Meta-Analysis: Relationship of History of Acute Respiratory Infections and Low Birth Weight with Stunting in Toddlers - Kharis Faridan; Meitria Syahadatina Noor; Alfi Yasmina; Syamsul Arifin; Harapan Parlindungan Ringoringo (Jurnal Berkala Kesehatan, 2021)
Basic Health Research (2018) and National Socio-Economic Survey (2019) showed a high incidence of stunting in Indonesia. History of acute respiratory infection (ARI) and low birth weight (LBW) were studied as factors associated with stunting in under-five children. The research’s objective was to analyze the association between the history of ARI and LBW with the incidence of stunting in under-five children. This study was a meta-analysis. Literature searching was conducted in reputed and accredited journals in PubMed and Google Scholar, published between 2016-2020, analytic observational study design, contained OR/PR/RR with 95% confidence interval, written in English or Indonesian, and available in full-text. The meta-analysis was conducted with RevMan 5.4 application. We included 14 studies. Results showed there was a significant association between history of ARI and the incidence of stunting in under-five children, with pooled OR = 2.48 (95%CI = 1.82-3.40, p < 0.00001, I2 = 0%, p for heterogeneity = 0.66). This study showed there was a significant association between LBW and incidence of stunting, with pooled OR = 2.15 (95% CI = 1.58-2.93, p < 0.00001, I2 = 61%, p for heterogeneity = 0.005). The conclusions were there were significant associations between the history of ARI and LBW with the incidence of stunting in under-five children.